In vitro study of antibacterial and osteogenic activity of titanium metal releasing strontium and silver ions. (January 2021) - Okuzu, Yaichiro; Fujibayashi, Shunsuke; Yamaguchi, Seiji; Masamoto, Kazutaka; Otsuki, Bungo; Goto, Koji; Kawai, Toshiyuki; Shimizu, Takayoshi; Morizane, Kazuaki; Kawata, Tomotoshi; Shimizu, Yu; Hayashi, Makoto; et al.
Peri-prosthetic infection and loosening of implants are major problems in orthopaedic and dental surgery. To address these issues, surface treatment methods for titanium implants have been improved by modifying the alkali and heat treatment. We have previously fabricated calcium-treated Ti metal that releases Sr ions (CaSr-Ti), which resulted in a higher in vitro osteogenic response and early in vivo bone bonding. Further, we developed a Ti metal that released both Sr and Ag ions (CaSrAg-Ti). In this study, we evaluated the antibacterial ability and osteogenic cellular response of CaSrAg-Ti and CaSr-Ti in vitro using rat bone marrow stromal cells (BMSCs) cultured on implant samples and extract mediums (EMs) made by immersing the implant samples in the medium. CaSrAg-Ti did not show cytotoxicity and was associated with a slightly higher osteogenic response when compared to CaSr-Ti, without inhibiting the effect of Sr. The osteogenic response was also observed in the cells cultured with the CaSrAg-Ti EM; however, the response was not as high as that of the cells on the CaSrAg-Ti implant sample. Significantly higher antibacterial activity was observed along with an antibacterial efficacy of more than 95% against methicillin-susceptible Staphylococcus aureus and Escherichia coli . The main advantages of our surface treatment are its simplicity and low cost. Therefore, our treatment is promising for clinical applications in orthopaedic or dental Ti-based implants with antibacterial and early bone-bonding abilities.